Stop hunt detection using indicators and expert advisors in the forex market. (March 2020) - Noertjahyana, A; Christopher, A; Abas, Z A; Yusoh, Z I M; Setiawan, A
Abstract: Foreign exchange trading activities are one of the businesses that can generate big profits, and provide freedom for business people without the need to provide a large capital. Traders often suffer losses due to uncertainty in the market. One of them is market manipulation carried out by brokers or banks. For this reason, this research was conducted to detect any manipulation that occurred in the foreign exchange market. This research tries to combine trading systems, indicators and expert advisors that aim to help traders detect fake market price movements to minimize losses that occur due to errors in making transaction decisions. The results of the study produce an indicator that is able to detect the potential of certain patterns used by the market maker to reverse the direction of market prices and is supported by the presence of expert advisors who are able to pinpoint potential market manipulation, so traders can avoid large losses.